Women’s Career Advancement Barriers in A Matrilineal Society: The Case of Minangkabau - Fitria, Fitria (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
This study seeks to examine and to compare the patterns of women’s and men’s career advancement in a municipal government located within traditional area of the biggest matrilineal society in the world, the Minangkabau. This research employed a qualitative approach through a case study and suggests that the higher the position, the less the number of women occupying it. Further, this study also aims to explore thebarriers that impede career advancement of the female employees. Women face barriers that become more significant as they climb the hierarchical structure, including lack of experience, job segregation, work-family conflicts, and stereotypes. Applying newpolicies such as a quota system and flexible work arrangements can be implemented to address these issues. This research only studied one municipal region within the Minangkabau. Future and more extensive research can provide a more comprehensive understanding of the situation by observing more local governments